Transdutor a fibra ótica para análise de biodiesel - Kawano, Marianne Sumie (2010)
This work presents a study of the applicability of long period gratings and long period gratings structures, written in silica optical fiber, when they are employed as a transducer of refractive index to analyze the biodiesel and their original oils. As samples were used: soybean oil, fried oil, sunflower oil, soybean oil biodiesel and biodiesel from sunflower oil. The experiments were performed using a conventional long period grating and a long period grating structure named as cascaded long period grating, in which a long period grating is employed on an interferometric configuration similar to a Michelson interferometer. Initially, were analyzed several samples of oil and biodiesel at room temperature. The results showed that when the devices were immersed in the different samples, which have refractive index equal or higher than that of the optical fiber cladding, the guiding light conditions no longer allow these devices for the use as a refractive index transducer. However, if the cascaded long period grating is used, when only the cavity of the Michelson interferometer or part of this cavity is placed in contact with samples, the devide shows a promising tool for checking the quality of biodiesel. Still trying to improve the performance of the cascade long period gratings, the samples were heated in order to modify their refractive index, making them smaller than the refractive index of the fiber cladding. The results showed that the systematic increase of the sample temperature is an efficient artifice for analysis of substances which refractive index, at room temperature, are equal of higher than that of the optical fiber cladding.